Perjanjian Pengusahaan Tanah Ulayat Oleh Perusahaan Dengan Masyarakat Hukum Adat di Indonesia - Dewi, I Gusti Ayu Gangga Santi; Adhi, Yuli Prasetyo; Prasetyo, Agung Basuki (PROGRESIF: Jurnal Hukum, 2023)
The national land law does not stipulate that the company's usufructuary rights can be cultivated on management rights land and customary law community land becomes management rights. This study aims to identify and analyze the process of ulayat land concession agreements by companies and the status of ulayat lands if the agreement between the company and customary law communities related to ulayat land concessions has ended and uses a normative juridical method, namely the data source used is secondary data, obtained from official documents, books and written reports. The results begin with a land use agreement, the status of communal land changes after the agreement expires with management rights to which the company's usufructuary rights apply for customary law communities.